Accounting for China's regional carbon emissions in 2002 and 2007: production-based versus consumption-based principles. (15th September 2015) - Liu, Lan-Cui; Liang, Qiao-Mei; Wang, Qian
Abstract: Analysing the characteristics of virtual carbon flows among regions is essential for China to deploy effective regional mitigation strategies. This study established a multi-regional input–output model to assess the characteristics of interregional carbon flows and account for carbon emissions by different regions according to one production-based and two consumption-based accounting principles. Results indicate that interregional carbon flows grew from 136.4 MtC in 2002 to 377.8 MtC in 2007. The proportion of total national emissions represented by interregional carbon flows rose from 15.2% in 2002 to 21.1% in 2007. Therefore, different accounting principles tend to have more and more different impacts on the emission responsibility that a region is assumed to take. According to the results under different accounting principles, the Northeast and Northwest regions will need to assume much greater emission responsibilities under the production-based principle than under either of the consumption-based principles. The Eastern Coastal and Southern Coastal regions, in contrast, will need to assume much greater emission responsibilities under the two consumption-based principles. Moreover, the carbon flows from the Central and Northwest regions to the Eastern Coastal region were the greatest contributors to both the total interregional carbon flows in 2007 and the growth in interregional carbon flows from 2002 to 2007. Given this situation and considering the economic disparity among these regions, methods similar to the Joint Implementation could be considered when discussing the regions' emission responsibilities. Results also indicate that the total use direct emission principle is a more feasible and practical consumption-based choice. Highlights: Interregional carbon flows are obvious and show an increasing trend. Different accounting principles evidently affect regional emission responsibility. Cooperation among regions could be adopted to reduce unfavourable economic impacts.